Nā’ilah Hāshim Ṣabrī : Tokoh Tafsir Wanita Abad Ke-21: Nā'ilah Hāshim Ṣabrī : 21st Century Female Tafsir Figure - Muhammad, Maslina; Abdullah, Mustaffa; Abd Razzak, Munirah (Journal Al-Muqaddimah, 2019)
This article introduces Nā'ilah Hāshim Ṣabrī through his work Mubṣir li Nūr al-Qur'ān, a modern interpretation of the work that has named Nā'ilah Hāshim Ṣabrī as the first female interpretation and the only one has succeeded in composing the work complete interpretation of 30 juz of the Quran. The main objective of this paper is to present the biography of Nā'ilah Hāshim Ṣabrī and the introduce her tafsir book al-Mubṣir li Nūr al-Qur’ān and to elaborate his interpretation methodology through the interpretation.This study uses two methods: historical and textual analysis as well as field studies. The finding of study show that Nailah's character as a mufassir focuses on the strength of the method of writing al-Mubṣir li Nūr al-Qur'ān and the interpretation methodology was based on the merging between the manhaj tafsir bi al-ma’thūr with manhaj tafsir bi al-ra’y al-maḥmūd which was known as the manhaj tafsir bi al-atharī al-naẓarī.